Changes in emergence phenology, fatty acid composition, and xenobiotic‐metabolizing enzyme expression is associated with increased insecticide resistance in the Colorado potato beetle. Issue 3 (16th October 2019) - Clements, Justin; Olson, Jake M.; Sanchez‐Sedillo, Benjamin; Bradford, Benjamin; Groves, Russell L.
Abstract: The Colorado potato beetle ( Leptinotarsa decemlineata ) is a major agricultural pest of solanaceous crops. An effective management strategy employed by agricultural producers to control this pest species is the use of systemic insecticides. Recent emphasis has been placed on the use of neonicotinoid insecticides. Despite efforts to curb resistance development through integrated pest management approaches, resistance to neonicotinoids in L. decemlineata populations continues to increase. One contributing factor may be alterations in insect fatty acids, which have multiple metabolic functions and are associated with the synthesis of xenobiotic‐metabolizing enzymes to mitigate the effects of insecticide exposure. In this study, we analyzed the fatty acid composition of L. decemlineata populations collected from an organic production field and from a commercially managed field to determine if fatty acid composition varied between the two populations. We demonstrate that a population of L. decemlineata that has a history of systemic neonicotinoid exposure (commercially managed) has a different lipid composition and differential expression of known metabolic detoxification mechanisms relative to a population that has not been exposed to neonicotinoids (organically managed). The fatty acid data indicated an upregulation of Δ 6 desaturase in the commercially managed L. decemlineata population and suggest a role for eicosanoids and associated metabolic enzymes as potential modulators of insecticide resistance. We further observed a pattern of delayed emergence within the commercially managed population compared with the organically managed population. Variations in emergence timing together with specific fatty acid regulation may significantly influence the capacity of L. decemlineata to develop insecticide resistance. Research Highlights: Organic and conventional management practices influence lipid compositions in the specialist herbivore Leptinotarsa decemlineata. Individuals resistant to imidacloprid overexpress known detoxification pathways relative to susceptible individuals. Abstract :   A commercially managed field population of Leptinotarsa decemlineata significantly overexpresses transcripts related to xenobiotic metabolism, including a cytochrome p450 6k1, ATP‐binding cassette subfamily G, and peroxidase‐like enzyme, when compared to an organically managed field population.